(untitled) (Praxis Educativa, 2026)
In recent decades, Latin America has seen strong growth in higher education, promoting its democratization. In this context, the University of the Republic of Uruguay included the goal of generalized university access in its 2020-2024 Strategic Plan. This research focuses on analyzing the coordination policies between secondary and higher education in Northeast Uruguay, an area historically lagging in terms of human development. Coordination practices such as guidance, academic preparation courses, and mentoring are explored. Through a qualitative approach, problems such as a lack of information about majors, academic difficulties, and a disconnect between educational offerings and young people’s interests were identified. Although some support practices have been implemented, the lack of curricular coordination between secondary and higher education remains a central challenge for students’ transition to and retention in university.